Psychology of athletes` dual careers: An overview of European research and selected projects - Stambulova, N. (The 15th European Congress of Sport and Exercise Psychology, 2019)
The aim of this presentation is twofold: (1) to trace an evolution of dual career (DC) research in Europe based on two consequent systematic review papers (Guidotti, Cortis, & Capranica, 2015; Stambulova & Wylleman, 2018), and (2) to provide a brief introduction to four European DC projects conducted in 2015-18. The two aforementioned reviews covered European DC research for 2007-14 (Guidotti et al.) and 2015-18 (Stambulova & Wylleman). The recent review compared to the previous one revealed the following trends: DC research in is intensified (more studies are published per year), DC term is well established, more studies are informed by a holistic lifespan perspective (Wylleman, Reints, & De Knop, 2013), still a lack of published research on DC in sport and work, but in terms of DC in sport and education three new concepts, 8 instruments, and 16 empirical frameworks (e.g., DC competency frameworks for athletes) have been introduced in the 2015-18 publications. Four European projects have been selected for this presentation to illustrate a continuity in the academic dialogues within the European DC discourse in regard to DC athletes` and support providers` competencies and related training. These projects include: "Gold in Education and Elite Sport" (GEES) funded by the EU (2015-16), "The development and evaluation of training modules for DC support providers: A European pilot" funded by the IOC (2017-18), "Be a Winner In elite Sport and Employment before after athletic Retirement" (B-WISER) and "Mind the Gap" - both funded by the EU (2017-18).